Coffee Wilt Disease: a major constraint to coffee production in Africa - Bieysse, D.; Lepoint, P.; Hakiza, G.; Kalonji, A.; Maraite, H. (CIRAD, 2006)
CWD was first observed on Coffea excelsa in Central Africa Republic (CAR) in 1927. From the 1940s to the 1960s the disease caused considerable destruction to C. excelsa and C. canephora in Central and West Africa, killing trees within two months to two years of the first appearance of symptoms. Systematic elimination of affected plants over vast areas and deployment of resistant varieties virtually eradicated CWD in these regions. However, in the late 1970s CWD “re-appeared” on C. canephora in Northeast Democratic Republic of Congo (DRC), and was subsequently reported in neighbouring Uganda (1993) and Tanzania (2000) causing renewed and extensive damage. In Uganda alone, where C. canephora accounts for 85% of exported coffee, CWD has destroyed 120 million (45%) trees and reduced the country’s share of the international market from 7% to 3% in just 10 years. C. arabica, although also cultivated in these countries, remains unaffected despite CWD having caused damage to C. arabica in Ethiopia since 1957
Keywords: Coffee Wilt Disease; coffee production